The Influence of Using Recycled Asphalt Pavement and Crumbed Rubber on Asphalt Pavement: A Review - Hashim, Sajjad; Al-Mosawe, Hasan; Mohammed, Haneen (Al-Nahrain Journal for Engineering Sciences, 2023)
Reclaimed (recycled) asphalt pavement (RAP), the most recycled material worldwide, is the mostly reclaimed material utilized in hot mix asphalt. Polymer (Crumb rubber) incorporation frequently leads to enhanced durability and resistance to heat cracking and rutting, two forms of permanent deformation. It also relieves stiffness and minimizes fatigue damage. This study aims to gather all previous RAP-related research and crumb rubber CR, so that the impact of using these materials on mechanical, physical properties of asphalt pavement, environmental effect and cost effective are clarify and explained. The finding of this research proved that the use of RAP and CR provide considerable structural and financial enhancements to the construction.